Analysis of the Digital Marketing Mix on the Mikhayla_Shop Account Reviewed from the Perspective of Islamic Business Ethics - Aini, Saqofa Nabilah; Romaisyah, Luqita; Agustin, Riska (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2023)
This study aims to examine the application of the digital marketing mix through the Instagram account of Mikhayla_Shop, a leading hijab retailer in Indonesia, from the perspective of Islamic Business Ethics. Using a qualitative descriptive approach, the study analyzes how each component of the marketing mix (7Ps: Product, Price, Promotion, Place, People, Process, and Physical Evidence) is implemented in alignment with key Islamic ethical principles: tawḥīd (divine unity), justice, free will, responsibility, and iḥsān (excellence). The findings reveal that Mikhayla_Shop's strategies demonstrate a unique integration of ethical values into modern digital marketing practices, maintaining transparency, fairness, and customer respect in all touchpoints. This research contributes to the growing discourse on ethical marketing in Muslim-majority digital economies by offering a context-based model of Sharia-compliant digital marketing strategy. It provides empirical grounding for the application of Islamic ethics in contemporary e-commerce environments. Future research may expand this framework across comparative cross-national studies, particularly in the emerging halal fashion industry, to explore the adaptability and scalability of Islamic ethical marketing practices in global digital marketplaces.